Gender in the 21st century - Sweetman, Caroline (Oxfam focus on gender., 2000)
"From the perspectives of development specialists and feminist activists, this book considers the challenges facing gender and development practitioners and policy-makers in the twenty-first century. Despite some successes, women in many countries remain in abject poverty, lacking food, clean water, education, and medical care. Women throughout the world are still economically, politically and socially marginalised, at a time when the globalisation of business, industry, and communications technology is radically changing our world."--Book jacket.